DAYA TARIK WISATA ALAM BUKIT DOA MAHAWU TOMOHON BERDASARKAN ASPEK PENGUNJUNG - Fince Aibekob; Fabiola B. Saroinsong; Martina A. Langi; Alfonsius Thomas (Universitas Sam Ratulangi, 2014)
ABSTRACT This research aims to know the profile, spreading, and the level of visitor’s satisfaction in tourism area of Bukit Doa of Mahawu Tomohon along the year of 2012 and 2013. The visitors spread is analysed based on monthy visit data during 2012-2013 for two years. The level of visitor’s satisfaction and development advice is got by interviewing and questioner filling.This research was done in natural tourism area of Bukit Doa of Mahawu in Tomohon, North Sulawesi province. The material used in this research is the questioner’s paper.The visitor’s profile is analysed based on the home, gender, age, education level, job, kind of vehicle, and the way to visit. The visitor’s perception about tourism fascination was got from the interview result and questioner filling. Based on the research done, the visitors of Tourism object of Bukit Doa of Mahawu are satisfyied enough and even come of them are very satisfyied. The amount of the visitors in the year of 2012 and 2013 were 90.327. The most visitors coming was on march 2013 that was 11.217 visitors while the least was on February 2013 that was only 4066 visitors.